(untitled) (International relations and international law Journal, 2021)
This article analyzes trends in international trade regarding trade contradictions and attempts to define “trade wars”. The growth of global trade has changed the economic impact and political contours of trade protection. The study revealed that today trade disputes and wars, which have turned into the biggest problems for the global trading system, this is a matter of great concern, and certain contradictions in trade relations between states are characterized as “trade wars”. Since the establishment and development of international trade relations, in the context of competition between countries for markets, serious trade conflicts have begun to arise and escalate, and in connection with the development of the international trading system, the consequences of trade clashes have become increasingly large-scale. Countries have used a variety of methods – from diplomacy to military intervention-to protect their own markets from foreign competitors ‘ goods and strengthen their positions in foreign markets. The article examines the history of development and the reasons of world trade wars. The study of the evolution of international trade contradictions and disputes from the time of Ancient Greece to the present day, showed that the objects of disputes were different, different methods and tools were used during trade wars. Although trade wars have always been destructive, at the present stage, these conflicts causing divisions can escalate into new geopolitical confrontations and lead to a prolonged global recession. Key words. trade and economic relations, trade contradictions, trade war, regulatory tools, USA, China.